Study on Implementation of Limited Protection Rules For Banggai Cardinalfish (Pterapogon kauderni) Which Is Transported Through The Province of Bali - NEGARA, I KETUT WIJA; Pradnyani, Ni Desak Nyoman; Safitri, Diah Ayu (Advances in Tropical Biodiversity and Environmental Sciences; Vol 7 No 1 (2023): ATBES, 2023)
The Banggai cardinalfish (Pterapogon kauderni) is a species of ornamental fish endemic to the Banggai Archipelago, Central Sulawesi, Indonesia. The high level of exploitation has caused the population of the proud fish to decline. The government seeks conservation by issuing KEPMEN KP Number 49 of 2018 concerning the Protection Status of Banggai cardinalfish. The purpose of this study/research is to determine the effectiveness of implementation after the policy is issued. Bali is one of the exit points for the export trade of the Banggai cardinalfish commodity. Banggai cardinalfish export from Bali in 2019-2020 only reached 60 thousand, increasing to 111 thousand fish with a frequency of 303 export data in 2021. Export destinations are the United Kingdom, France, China, Taiwan, Hongkong, Denmark, Netherlands, Brazil, Poland, and Germany. Banggai cardinalfish in its trade must be free from disease infections, listed in the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia No. 17 of 2021. Commodities must be examined by checking for types of quarantine fish diseases, namely Megalocytivirus infection. The prevalence value of Megalocytivirus or Banggai Cardinal Iridovirus (BCIV) from Banggai cardinalfish to exporters in Bali in 2020 was 1.49 and in 2021 it was 4.10. The current condition of the Banggai fishery in its utilization must meet the requirements attached to the Indonesian Minister of Maritime Affairs and Fisheries Decree No. 21 of 2021 regarding quotas, and Government Regulation Number 85 of 2021 regarding PNBP rates.